2008
DOI: 10.1016/j.jacc.2008.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Endothelial Cells Purified From Human Skeletal Muscle Improve Cardiac Function After Transplantation Into Infarcted Myocardium

Abstract: Objective The aim was to evaluate the therapeutic potential of human skeletal muscle-derived myoendothelial cells for myocardial infarct repair. Background We have recently identified and purified a novel population of myoendothelial cells from human skeletal muscle. These cells co-express myogenic and endothelial cell markers and produce robust muscle regeneration when injected into cardiotoxin-injured skeletal muscle. Methods Myoendothelial cells were isolated from biopsies of human skeletal muscle using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…These cells exhibit a superior potential in sustaining cardiac function after acute myocardial infarction than myoblasts and endothelial cells. 7,54 The injection of myoendothelial cells significantly induced neoangiogenesis and reduced fibrosis in infarcted mouse hearts. 54 Pericytes, with their inherent actions on the vasculature 8 and recently documented multipotency, seem to match the scope of ideal cells for cardiac repair.…”
Section: Pericytes: Applications In Tissue Repair and Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells exhibit a superior potential in sustaining cardiac function after acute myocardial infarction than myoblasts and endothelial cells. 7,54 The injection of myoendothelial cells significantly induced neoangiogenesis and reduced fibrosis in infarcted mouse hearts. 54 Pericytes, with their inherent actions on the vasculature 8 and recently documented multipotency, seem to match the scope of ideal cells for cardiac repair.…”
Section: Pericytes: Applications In Tissue Repair and Regenerationmentioning
confidence: 99%
“…7,54 The injection of myoendothelial cells significantly induced neoangiogenesis and reduced fibrosis in infarcted mouse hearts. 54 Pericytes, with their inherent actions on the vasculature 8 and recently documented multipotency, seem to match the scope of ideal cells for cardiac repair. By using purified skeletal muscle pericytes, we designed a series of experiments to determine the potential of these cells for cardiac repair/regeneration.…”
Section: Pericytes: Applications In Tissue Repair and Regenerationmentioning
confidence: 99%
“…After isolation, stem cells derived from skeletal muscle may be easily expanded under in vitro conditions. The most frequently used medium is Dulbecco's modified Eagle medium (D-MEM) supplemented with fetal bovine serum and/or horse serum in varying concentrations [34,59]. Several authors supplemented their media with chick embryo extract or various growth factors (e.g.…”
Section: Isolation and Culture Of Muscle Derived Stem Cellsmentioning
confidence: 99%
“…Several authors demonstrated the potential of stem cells derived from skeletal muscles to differentiate into cardiomyocytes [41,76]. Okada et al [59] injected populations of myogenic endothelial cells into immune-deficient mice with induced acute myocardial infarction. They observed improvement in left ventricular function six weeks after administration.…”
Section: Regeneration Of Cardiac Musclementioning
confidence: 99%
See 1 more Smart Citation